Experimental study on seismic behavior of lead-rubber bearing considering bi-directional horizontal input motions. (1st November 2019) - Kim, Jung Han; Kim, Min Kyu; Choi, In-Kil
Highlights: Full-scale lead rubber bearings were tested by 2-D horizontal input motions. 2-D test motion with isolation frequency should be applied for rubber type isolator. The failure strain level by 2-D test decreased 20% lower compared to 1-D test.